PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN TERHADAP EFEKTIVITAS PELAPORAN KEUANGAN (Studi Kasus Pada Warung Makan Lesehan Brodin Kertosono) - Sulistiyani, Rika Mbir; Subagyo, Subagyo; Widodo, Moch. Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research was conducted with the aim of knowing and analyzing the implementation of the Regional Management Information System (SIMDA) in the quality of preparing financial reports at Warung Makan Lesehan Brodin Kertosono. The approach used is qualitative with the type of case study (case study research). The research respondents consisted of two people who were shop managers and cashier employees. Respondents were chosen because they are considered to have information and are related to activities related to stall finance. The research data was collected through the process of observation and interviews, and analyzed using the data triagulation method. The results of the study indicate that SIMDA Finance has been applied in the financial management process of the warung although it is still based on simple criteria. The SIMDA Finance process is carried out from the collection of transaction data which will then be inputted into the system by the cashier which in each period will be reported in the form of the difference between income and expenses within a certain period (similar to a profit/loss report). From the results of this study, it is hoped that business actors and prospective actors will prepare and implement SIMDA Finance in managing their businesses to facilitate the process of recording and measuring the financial condition of their business.